Antioxidant peel off mask formulation of tamarind seeds ethanol extract - Putri Djatmiko Marchia Afifah; Veranita Weri; Wardani Siska Tatiana (LPPM Universitas Duta Bangsa Surakarta, 2021)
The human body does not have excess reserves of antioxidants, so if a lot of radicals are formed, the body needs exogenous antioxidants. In an effort to get healthy skin we also must not forget about antioxidants to protect our skin. The adequacy of antioxidants is a bulwark to prevent the harmful effects of free radicals that damage the skin. But there are concerns about the possible side effects that have not been known from synthetic antioxidants, causing natural antioxidants to become a much needed alternative, one of which comes from plants. One plant that has antioxidant properties is tamarind seeds. Tamarindus indica L seeds contain polyphenol compounds and high antioxidant potential. The methanol extract of tamarind seeds has a higher content of polyphenol compounds and antioxidant potential than the methanol extract of other parts of the Tamarindus indica plant. Based on antioxidant research, the ethanol extract of tamarind seeds has an IC50 value of 40.21 ± 4.07262. The purpose of this study was to formulate an antioxidant peel off mask from tamarind seed extract using ethanol solvent with the maceration method. Furthermore, the extract obtained was formulated into a peel off preparation using 3 formulas with 5%, 10%, and 15% concentrations, respectively. The preparation is then tested for the evaluation of organoleptic preparations, homogeneity, pH, viscosity and flow properties, dispersibility, drying time, stability test, and irritation test